Role of Gamma Interferon in Helicobacter pylori-Induced Gastric Inflammatory Responses in a Mouse Model - Sawai, Naoki (American Society for Microbiology, 1999)
The immune responses to Helicobacter pylori infection play important roles in gastroduodenal diseases. The contribution of gamma interferon (IFN-γ) to the immune responses, especially to the induction of gastric inflammation and to protection from H. pylori infection, was investigated with IFN-γ gene knockout (IFN-γ(−/−)) mice. We first examined the colonizing abilities of eight H. pylori strains with a short-term infection test in order to select H. pylori strains which could colonize the mouse stomach. Only three strains (ATCC 43504, CPY2052, and HPK127) colonized C57BL/6 wild-type mice, although all of the strains except for ATCC 51110 could colonize IFN-γ(−/−) mice. The number of H. pylori organisms colonizing the stomach in wild-type mice was lower than that in IFN-γ(−/−) mice. Oral immunization with the CPY2052 sonicate and cholera toxin protected against infection with strain CPY2052 in both types of mouse. These findings suggested that IFN-γ may play a protective role in H. pylori infection, although the degree of its protective ability was estimated to be low. In contrast, in a long-term infection test done to examine the contribution of IFN-γ to gastric inflammation, CPY2052-infected wild-type mice developed a severe infiltration of mononuclear cells in the lamina propria and erosions in the gastric epithelium 15 months after infection, whereas CPY2052-infected IFN-γ(−/−) mice showed no inflammatory symptoms. This result clearly demonstrated that IFN-γ plays an important role in the induction of gastric inflammation caused by H. pylori infection.